A criação da criança: letra e gozo nos primórdios do psiquismo - Jerusalinsky, Julieta (2009)
This thesis approaches the production of the inscriptions that constitute the psychism in mother-baby ties. The text is present within the field of fundamental psychopathology and theoretical-clinical psychoanalysis. The author posits that the inscription of the letter a concept employed by Jacques Lacan to situate psychic inscriptions depends on the mother's involvement in the baby's economy of jouissance. The transmission of the inscription does not take place through the direct presence of a code, but rather through a succession of enigmatic effects on the baby's ties with his mother. She is an embodied mOther, in view of which the subject must emerge on the border between jouissance and knowledge, body and language. On the basis of the given-to-be-seen on the baby's body, the mother formulates the supposition of the knowledge of which the baby is a tributary. It is knowledge of the mother's desire and is enigmatic to the mother herself, but the baby becomes involved in it. The givento- be-seen on the baby's body takes on the character of a formation of the unconscious. The mother's psychism operates there as an initially prosthetic psychic apparatus for the baby to function physically. The baby s economy of jouissance is thus bound to its mother's knowing. The earliest roots of psychic constitution thus reveal the lack of correspondence between body and subject. Through her care, the mother "embroiders" the letter on the baby's body as she occupies herself with his economy of jouissance, by being affected by what affects him. She thus links the baby's physical functioning to a language structure by which he inadvertently becomes involved in the tie with the mOther. From then on, the tie is indispensable in his circuit of satisfaction. For this reason, the baby is also affected by the sounds and lalangue through which the mother's jouissance emerges in the act of enunciation. When the baby becomes emotionally involved in the games that constitute the subject, the mother attributes their authorship to him, and the knowledge of this playing permanently transits with him through the positions of object and subject. She presumes that he is the subject that knows about playing. At the same time, when she makes the baby an object of jouissance, she herself obtains jouissance by transitively identifying with the jouissance of the baby's passivity. Therefore, the jouissance involved in the tie between mother and baby is not reduced to either the anxiety of insufficiency nor to the measure of phallic strength, nor even to the masochistic jouissance of the mater dolorosa. Through jouissance located beyond the phallic, a creation can be produced, a child can be raised. The raising of the child indicates the transitivist dimension of the earliest roots of the tie between mother and baby. If motherhood can make room for an act that, for a woman, is creative, the child, in turn, has a way to be creative when playing. The relationship between mother and baby is limited neither to phallic jouissance nor to the search for complementarity with the jouissance of the mOther, but it can open the way to an Other jouissance, a supplementary creation, which, even if it makes use of the paternal function, does not stop at the Oedipus complex. In view of the mental suffering involved when a baby painfully gives-to-be-seen on his body, the clinician intervenes, not by observing but by reading, which can decipher. Operating on the basis of the key to the code, the letter, which insists on symptomatic repetition, the clinician opens the way to supplementary creations